DESAIN SISTEM PESANTREN DALAM MENINGKATKAN PERFORMA PENDIDIKAN ISLAM DI PP AL-HUSEN BANGKES KADUR PAMEKASAN - Khalik, Abd (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2017)
Design management of educational boarding school in enhancing the value of education schools in Al-Husen have been done in some various ways: a) Holding change management model of education that is applied, b) Changes at the structure of personnel management, c) Organize the implementation and application refinement of educational programs, d) Conducting services repair and curriculum improvement, e) Conducting administrative system changes. The constraints faced in the implementation of educational management boarding schools are a) pattern of the management of the schools are still using a traditional system or old patterns such as administration disorderly, b) adopting a "Mono" (singular), c) Loyalty to the scholars who excess, d) infrastructure is inadequate boarding institutions, e) the low quality of human resources. Based on some of these obstacles then an alternative solution which is done in order to face the obstacles of educational regimes management schools in enhancing the value of education schools in Al-Husen boarding school are a) holding a renewal and exists innovation, b) Hold a change of management in order to compensate for the changes and demands of the future ahead, c) opinion when meeting that the system is applied in order to be change , d) educate the teachers who have undergraduate (S1). Thus the expected results of this research can be an input for the entire academic community in al-Husen boarding school, so they can understand quickly, especially for the education improvement. Based on the results of research that researchers do, it can be noted in this study.